From Silvio Pellico to Selahattin Demirtaş: prison literature and literary polemics in Turkey - Mignon, L (Penn State University Press, 2024)
Selahattin Demirtaş's fiction has led to some fierce discussions in the literary world in Turkey. The polemics were a reminder that prison literature, broadly defined, always was a hotly debated genre in the literary sphere of the late Ottoman Empire and the Republic of Turkey. Indeed, the publication of a Turkish translation of a classic example of the genre—namely Silvio Pellico's Le mie prigioni, translated by Recaizade Mahmut Ekrem in 1874—caused a vivid reaction by the Young Ottoman reformer Namık Kemal. This article looks at how the debate on the partial Turkish translation of Pellico's memoirs that combined both aesthetic concerns and political sensitivities is not without similarities with debates about Demirtaş's literary work. After a first part outlining varied responses to Demirtaş's short stories and novels, the article analyses Namık Kemal's "Mes prisons Muahazanamesi" (A Criticism of Mes prisons) and brings to the fore those aspects that were to become characteristic for future literary polemics. That Pellico's first Ottoman Turkish critic should have been himself an author and activist who was repressed, incarcerated, and exiled for his political views and engagement, shows how essential prison literature was in the development of modern literature in Turkish.